Cybersecurity for MBAs: Pi-shaped Course Design (Journal of The Colloquium for Information Systems Security Education, 2016)
This article addresses the need for cybersecurity-savvy business leaders by describing the design of a cybersecurity course for students pursuing the MBA and other business degrees. Design drivers and the context for delivery led to a unique pi-shaped course design. The top horizontal bar of the pi symbol represents cybersecurity scope: students gaining an understanding of the breadth of the subject with guiding frameworks and models. The two vertical legs in the pi symbol provide opportunities for students to achieve depth: (1) cyber assess, for student teams to assess the cybersecurity state of a real organization, and (2) cyber brief, for teams to conduct research and analysis on specific cybersecurity topics of interest. Experiences with offering the course are discussed, with lessons learned and recommendations for continued improvement.
Keywords: Education; Security; Security Management; MBA